Radioimmunoassay of tuberculoprotein derived from Mycobacterium tuberculosis. - Straus, E (1980)
A radioimmunoassay was developed for constituent of the purified-protein derivative obtained from cultures of Mycobacterium tuberculosis. Crossreacting immunoreactive material was detected in cultures of other mycobacterial species, but no immunoreactivity was present in cultures of various fungal and bacterial species. The development of specific radioimmunoassays for tuberculoproteins offers a new research and diagnostic approach.